Implikasi Kekerasan Verbal Orang Tua terhadap Sosial Emosional Anak Usia Dini 3-6 Tahun - Keken Putri Rahayu; Ismaniar Ismaniar; Lili Dasa Putri (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This article examines the implications of parental verbal violence on the socio-emotional development of early childhood aged 3–6 years. The study was conducted through an extensive literature review supported by general field observations in community settings. The purpose of this research is to describe the phenomenon of verbal violence experienced by young children, analyze its effects on their emotional security, self-confidence, and social adaptation, and identify contributing factors from both the family environment and parental characteristics. Using a qualitative descriptive approach, relevant books, journal articles, and institutional reports were synthesized to construct a comprehensive understanding of how negative communication patterns shape children’s socio-emotional development. The findings indicate that verbal violence such as yelling, scolding, insulting, labeling, and threatening can disrupt children’s emotional regulation, lower their self-esteem, and hinder their ability to interact positively with peers. Repeated exposure to harsh language also increases the risk of anxiety, aggression, and social withdrawal. Conversely, positive, supportive, and empathetic parental communication fosters emotional resilience, empathy, and healthy social behavior. This article highlights the urgent need for parents, educators, and communities to strengthen awareness regarding the harmful impact of verbal violence and to promote nurturing communication practices that support the holistic development of young children.